1996
DOI: 10.1093/bja/76.2.258
|View full text |Cite
|
Sign up to set email alerts
|

Central nuclei and spinal pathways in feedback inhibitory spinal cord potentials in ketamine-anaesthetized rats

Abstract: It has been suggested that heterosegmentally activated slow positive potentials (HSP), recorded from the spinal cord of rat and humans, are feedback inhibitory potentials. The present study was carried out to define ascending and descending spinal tracts and the sites of central nuclei involved in the production of these HSP, and the effects of ketamine on these central nuclei. The spinal cords in ketamine-anaesthetized rats were transected to determine the ascending and descending tracts involved in the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…Spinal transection by surgery and administration of drugs have proved this theory (17)(18)(19). Anesthetics are suggested to block the descending inhibitory action and thus modulate neuronal activities in the dorsal horn (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Spinal transection by surgery and administration of drugs have proved this theory (17)(18)(19). Anesthetics are suggested to block the descending inhibitory action and thus modulate neuronal activities in the dorsal horn (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…This study, however, demonstrated that the P2 wave was always inhibited by DCS. These different results may be due to the effects of ketamine on supraspinal structures, distinct from the wakeful state (19), because the effects of DCS on the N1 wave Figure 2. The effects of isoflurane and spinal cord transection on the conditioned inhibition of the segmental spinal cord potential (sgSCP) by dorsal column stimulation (DCS).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations